Science E-Modules in the Digital Era: A Bibliometric Analysis of Research Trends and Thematic Development - Maghfiroh, Ana Nailatul; Ellianawati (Jurnal Paedagogy, 2026)
This study aims to analyze the trends and characteristics of research related to e-module learning media in science education through a bibliometric analysis approach. The research employs a descriptive quantitative method with a bibliometric design. Data were obtained from scientific articles indexed in several academic databases, including Scopus, Web of Science, DOAJ, and Google Scholar, through a systematic search using keywords related to e-modules and science learning. Articles meeting the inclusion and exclusion criteria were analyzed using Bibliometrix software (R-Studio) and VOSviewer. Data analysis includes publication productivity, annual trends, top citation analysis, author collaboration, dominant keywords, and research theme mapping. The results show that publications related to science e-modules have significantly increased in the last five years, with the peak of publications occurring in 2024. The most cited articles are dominated by SINTA-accredited national journals and generally examine the development of e-modules based on the ADDIE model with contextual, scientific, connected, and guided discovery approaches. Dominant keywords such as e-module, science learning, digital learning, and STEM indicate a shift in research focus toward technology integration and the strengthening of 21st-century skills. Thematically, science e-modules are widely developed to improve media validity, learning independence, science literacy, critical thinking, and student learning outcomes. These findings provide a comprehensive overview of the developmental direction of science e-module research and serve as a basis for developing more effective and contextual learning media research and innovation in the future.